2014
DOI: 10.1155/2014/987956
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Fibre Polylactide Acid Composite with Empty Fruit Bunch: Chopped Glass Strands

Abstract: Hybrid polylactide acid (PLA) composites reinforced with palm empty fruit bunch (EFB) and chopped strand E-glass (GLS) fibres were investigated. The hybrid fibres PLA composite was prepared through solution casting followed by pelletisation and subsequent hot compression press into 1 mm thick specimen. Chloroform and dichloromethane were used as solvent and their effectiveness in dissolving PLA was reported. The overall fibre loading was kept constant at volume fraction, Vf, of 20% while the ratio of EFB to GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Glass fibers chopped into lengths of 3 and 6 mm were mixed with the PLA–oil palm fiber pellets and the mixture was compression molded at 165°C to melt the PLA and form composites. Figure shows the digital images of the hybrid composites with 20, 10, and 0% EPB: glass fiber loading . Tensile properties and flexural strength of the composites with varying levels of glass fibers were prepared using two different solvents demonstrated that the optimal fiber content was about 15% for both the samples.…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glass fibers chopped into lengths of 3 and 6 mm were mixed with the PLA–oil palm fiber pellets and the mixture was compression molded at 165°C to melt the PLA and form composites. Figure shows the digital images of the hybrid composites with 20, 10, and 0% EPB: glass fiber loading . Tensile properties and flexural strength of the composites with varying levels of glass fibers were prepared using two different solvents demonstrated that the optimal fiber content was about 15% for both the samples.…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
“…Tensile properties and flexural strength of the composites with varying levels of glass fibers were prepared using two different solvents demonstrated that the optimal fiber content was about 15% for both the samples. Chloroform dissolved samples provided better properties due to better solubility of PLA and lower viscosity and better wetting . Instead of using poly(lactic acid), recycled polypropylene was used as the matrix and chopped glass fibers (2–4 mm) and OPEFB fibers (2–4 mm) were used as reinforcement.…”
Section: Lignocellulosic Fibers As Reinforcementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tshai et al [14] investigated the mechanical properties of chopped strand E-glass and empty fruit bunch palm reinforced polylactide acid composites. Composites were fabricated by solution casting followed by palletization and hot compression.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric composites with various natural reinforcements (e.g., natural fibres, woods, and hybrid fibres) received significant attention in numerous applications including automotive and construction industries [1,2]. However, the application of natural fibre composites usually intended for interior application; one of the main reasons is degradation of mechanical properties of natural fibre composites in the presence of water.…”
Section: Introductionmentioning
confidence: 99%